HARDWARE AND SOFTWARE ARCHITECTURES FOR RECONFIGURABLE TIME-CRITICAL CONTROL TASKS - Piłat, Adam; Grega, Wojciech (Computer Science, 2013)
The most popular configuration of the controlled laboratory test-rigs is the personalcomputer (PC) equipped with the I/O board. The dedicated software components allowsto conduct a wide range of user-defined tasks. The typical configuration functionality canbe customized by PC hardware components and their programmable reconfiguration. Thenext step in the automatic control system design is the embedded solution. Usually, thedesign process of the embedded control system is supported by the high-level software. Thededicated programming tools support multitasking property of the microcontroller by selectionof different sampling frequencies of algorithm blocks. In this case the multi-layer andmultitasking control strategy can be realized on the chip. The proposed solutions implementrapid prototyping approach. The available toolkits and device drivers integrate system-leveldesign environment and the real-time application software, transferring the functionality ofMATLAB/Simulink programs to PCs or microcontrolers application environment.